Sex and the City: On the Politics of Producing Identities through Space - Castro, Maria Victoria; Buchely, Lina (ACME, 2023)
This paper explores the role of safety and sexual harassment risk as the pivotal element for the understandings in gender and city debates both in literature and in public policy in Colombia, which derives from understanding women’s sexuality as either “kind mothers” or “chaste women” who must protect their sexuality in public spaces. Using ethnographic techniques in Barranquilla and Cali (Colombia), we suggest that the protection of sexuality is tangential to women’s concerns when thinking about mobility, public space, and urban dimensions. We argue that putting women’s sexuality at the center of public concerns by using space governance techniques helps reproduce a power scheme in which women lose because they are seen as childlike, vulnerable, and requiring protection. We defend the idea that we need to think spatially, but differently: using a legal geographies approach allows a novel tool to imagine refining policy approaches about vulnerable subjectivities in urban spaces. This paper reveals how space operates as a mechanism to produce identities associated with the mobility experiences of its inhabitants and related with class and gender axes. We argue that the emphasis on sexual harassment as the organizing vector of the interventions related to gender and the city reproduces gendered stereotypes of women and men and reinforces and legitimizes the role of the nation-state as patriarchal protector. Further, the emphasis on safety fails to recognize different ways in which women use their sexuality in cities, their agency, and their strategies for negotiating with governance techniques.